Strengthen PSNP Institutions and Resilience Phase II (SPIR II), Ethiopia: Group Problem Management Plus (g-PM+) Pilot Screening Survey - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
The study's objective is to estimate the impact of group Problem Management Plus (GPM+), with and without a lump-sum cash transfer, on mental health, daily activities, and economic outcomes among Productive Safety Net Program (PSNP) clients in the regions of Amhara and Oromia. The population for this study consists of individuals residing in Amhara and Oromia who are registered and assisted by the PSNP public works program. Moreover, to be eligible, individuals must show signs and symptoms of depression or dysfunction, be between 18 and 59 years old, and be the main decision-maker or spouse of the main decision-maker. The impact of GPM+ will be assessed through a two-stage cluster randomized control trial (cRCT) design. The data included here comprise the results of a mental health screening, from which we identified respondents who were eligible for our study, and a baseline survey that includes measured characteristics of eligible respondents. These characteristics include household-level indicators such as food security and household consumption, and respondent-level indicators such as mental health outcomes. Per household, up to two people aged 18-59 years are screened (the primary decision-maker and spouse). The screening survey assesses depression and functionality using the Patient Health Questionnaire (PHQ-9) and the WHO Disability Assessment Schedule 2·0 (WHODAS). Data are organized by modules. In the screening data, Module A is at the household level, and Module B is at the respondent level.